Unravelling the Impact of Physical Activity on Postural Stability: An Experimental Study of University Students - Firdaus Hendry Prabowo Yudho; Fahmy Fachrezzy; Firmansyah Dlis (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to investigate the effects of physical activity interventions within a college physical education curriculum on postural stability control in adolescent females, while also serving as a follow-up study on the inclinometer sensor measurement tool currently under development. The research sample consisted of 35 healthy and active female students, with a mean age of 18.9 years (SD ± 0.832) and a mean BMI of 20.9 (SD ± 4.36).  This study focused on assessing postural stability through a series of standing scenarios: bipedal (Bi), unipedal (Uni), and tiptoe (Tip), each lasting 10 seconds per test. These tests utilized an inclinometer sensor to accurately measure balance and stability in each posture. The scenarios were designed to challenge various aspects of postural control, providing a comprehensive evaluation of the participants' ability to maintain stability under different conditions. The data in this study focused on the Mean (M) ± values derived from 100 readings recorded by the sensor as it measured the participants' tilt tendencies during a 10-second period, and the Standard Deviation (SD) values as the recorded outcome of their body sway stability. The study's analysis revealed significant changes between pre-test and post-test results, with decreased means, increased variability, and notable performance fluctuations. The Friedman and Wilcoxon tests confirmed significant differences across multiple variables, indicating that the intervention had a substantial and consistent impact on measurement outcomes across all groups.  The study found a significant improvement in participants' postural stability, particularly in the sagittal plane. Initially leaning forward, their posture became more stable and upright after 16 sessions of the physical education program. Stability in the frontal plane also improved, showing that the intervention had a positive impact on their overall postural control, both in terms of body tilt angles and body sway stability.